In the shadow of the river - Gabhart, Ann H., 1947- (Revell, a division of Baker Publishing Group, 2023)
"Jacci Reed loves her life on the Ohio River in 1896 as part of the Kingston showboat family, but shadows of her past and the death of her mother linger in her memory. With the help of the showboat owners' son, can she find answers before those shadows overtake her and threaten her life?"--